Induced Formation of Structural Domain Walls and Their Confinement on Phase Dynamics in Strained Manganite Thin Films. Issue 52 (29th October 2018) - Feng, Qiyuan; Jin, Feng; Zhou, Haibiao; Wang, Lingfei; Meng, Wenjie; Zhang, Kexuan; Wang, Jihao; Zhang, Jing; Hou, Yubin; Lu, Qingyou; Wu, Wenbin
Abstract: Domain walls (DWs) in strongly correlated materials have provided fertile ground for the discovery of exotic phenomena, and controlling the formation of DWs is still a challenge. Here, it is demonstrated that a new type of structural DW can be induced in a series of manganite thin films, which are engineered to achieve a robust charge‐ordering insulating (COI) ground state by selecting various films and substrates. The monoclinic domains are somewhat irregular in shape, and the corresponding DWs, taking the shape of closed loops, are ferromagnetic and metallic (FMM) at low temperatures. Remarkably, the DWs exhibit little dependence on temperature or magnetic field, due to the structural origins of the domains. Additionally, using magnetic force microscopy, the role played by DWs in the dynamics of the COI and FMM phases at the mesoscopic scale is revealed. They function as barriers, strictly confining the phase dynamics within each domain, reflecting the strong coupling of electronic phases with the lattice. Each domain exhibits binary occupation by a single pure phase, resulting in a quasi‐periodic phase separation. The universal behaviors of the multiple engineered films elucidate the possibility of controlling the formation of DWs and tuning phase dynamics through DW design. Abstract : A structural domain wall is induced in a series of manganite films with robust charge‐ordering insulating ground states. These ferromagnetic and metallic domain walls show no temperature‐ or magnetic field dependence, and interestingly, they can act as functional barriers to strictly constrain the phase dynamics, arising from the structural origin.